Nivolumab plus ipilimumab versus sunitinib in first-line treatment for advanced renal cell carcinoma: extended follow-up of efficacy and safety results from a randomised, controlled, phase 3 trial. Issue 10 (October 2019) - Motzer, Robert J; Rini, Brian I; McDermott, David F; Arén Frontera, Osvaldo; Hammers, Hans J; Carducci, Michael A; Salman, Pamela; Escudier, Bernard; Beuselinck, Benoit; Amin, Asim; Porta, Camillo; George, Saby; et al.
Summary: Background: In the ongoing phase 3 CheckMate 214 trial, nivolumab plus ipilimumab showed superior efficacy over sunitinib in patients with previously untreated intermediate-risk or poor-risk advanced renal cell carcinoma, with a manageable safety profile. In this study, we aimed to assess efficacy and safety after extended follow-up to inform the long-term clinical benefit of nivolumab plus ipilimumab versus sunitinib in this setting. Methods: In the phase 3, randomised, controlled CheckMate 214 trial, patients aged 18 years and older with previously untreated, advanced, or metastatic histologically confirmed renal cell carcinoma with a clear-cell component were recruited from 175 hospitals and cancer centres in 28 countries. Patients were categorised by International Metastatic Renal Cell Carcinoma Database Consortium risk status into favourable-risk, intermediate-risk, and poor-risk subgroups and randomly assigned (1:1) to open-label nivolumab (3 mg/kg intravenously) plus ipilimumab (1 mg/kg intravenously) every 3 weeks for four doses, followed by nivolumab (3 mg/kg intravenously) every 2 weeks; or sunitinib (50 mg orally) once daily for 4 weeks (6-week cycle). Randomisation was done through an interactive voice response system, with a block size of four and stratified by risk status and geographical region. The co-primary endpoints for the trial were overall survival, progression-free survival per independent radiology review committee (IRRC), and objective responses per IRRC in intermediate-risk or poor-risk patients. Secondary endpoints were overall survival, progression-free survival per IRRC, and objective responses per IRRC in the intention-to-treat population, and adverse events in all treated patients. In this Article, we report overall survival, investigator-assessed progression-free survival, investigator-assessed objective response, characterisation of response, and safety after extended follow-up. Efficacy outcomes were assessed in all randomly assigned patients; safety was assessed in all treated patients. This study is registered with ClinicalTrials.gov, number NCT02231749, and is ongoing but now closed to recruitment. Findings: Between Oct 16, 2014, and Feb 23, 2016, of 1390 patients screened, 1096 (79%) eligible patients were randomly assigned to nivolumab plus ipilimumab or sunitinib (550 vs 546 in the intention-to-treat population; 425 vs 422 intermediate-risk or poor-risk patients, and 125 vs 124 favourable-risk patients). With extended follow-up (median follow-up 32·4 months [IQR 13·4–36·3]), in intermediate-risk or poor-risk patients, results for the three co-primary efficacy endpoints showed that nivolumab plus ipilimumab continued to be superior to sunitinib in terms of overall survival (median not reached [95% CI 35·6–not estimable] vs 26·6 months [22·1–33·4]; hazard ratio [HR] 0·66 [95% CI 0·54–0·80], p<0·0001), progression-free survival (median 8·2 months [95% CI 6·9–10·0] vs 8·3 months [7·0–8·8]; HR 0·77 [95% CI 0·65–0·90], p=0·0014), and the proportion of patients achieving an objective response (178 [42%] of 425 vs 124 [29%] of 422; p=0·0001). Similarly, in intention-to-treat patients, nivolumab and ipilimumab showed improved efficacy compared with sunitinib in terms of overall survival (median not reached [95% CI not estimable] vs 37·9 months [32·2–not estimable]; HR 0·71 [95% CI 0·59–0·86], p=0·0003), progression-free survival (median 9·7 months [95% CI 8·1–11·1] vs 9·7 months [8·3–11·1]; HR 0·85 [95% CI 0·73–0·98], p=0·027), and the proportion of patients achieving an objective response (227 [41%] of 550 vs 186 [34%] of 546 p=0·015). In all treated patients, the most common grade 3–4 treatment-related adverse events in the nivolumab and ipilimumab group were increased lipase (57 [10%] of 547), increased amylase (31 [6%]), and increased alanine aminotransferase (28 [5%]), whereas in the sunitinib group they were hypertension (90 [17%] of 535), fatigue (51 [10%]), and palmar-plantar erythrodysaesthesia (49 [9%]). Eight deaths in the nivolumab plus ipilimumab group and four deaths in the sunitinib group were reported as treatment-related. Interpretation: The results suggest that the superior efficacy of nivolumab plus ipilimumab over sunitinib was maintained in intermediate-risk or poor-risk and intention-to-treat patients with extended follow-up, and show the long-term benefits of nivolumab plus ipilimumab in patients with previously untreated advanced renal cell carcinoma across all risk categories. Funding: Bristol-Myers Squibb and ONO Pharmaceutical.